2010
DOI: 10.1097/mpa.0b013e3181bd604e
|View full text |Cite
|
Sign up to set email alerts
|

Robotic and Laparoscopic Pancreaticoduodenectomy

Abstract: Complex procedures such as PD can be accomplished with minimally invasive surgical techniques using robotic instrumentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 17 publications
3
68
0
5
Order By: Relevance
“…Postoperative pancreatic fistula was identified in 9 patients in the laparoscopy-assisted (1-3, 12-18). Recent reports note that complete laparoscopic PD including laparoscopic resection and reconstruction is both technically feasible and safe (3)(4)(5)(6)(7)(8)19). In some cases a minilaparotomy of a few cm is necessary to remove the resected specimen.…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative pancreatic fistula was identified in 9 patients in the laparoscopy-assisted (1-3, 12-18). Recent reports note that complete laparoscopic PD including laparoscopic resection and reconstruction is both technically feasible and safe (3)(4)(5)(6)(7)(8)19). In some cases a minilaparotomy of a few cm is necessary to remove the resected specimen.…”
Section: Resultsmentioning
confidence: 99%
“…1 Port positioning during robotic-assisted pancreatico-duodenectomy. C is the 12-mm camera port, R1, 2, 3 are the 8-mm operative robotic ports, A1 is the 12-mm assistant port, A2 is the 5-mm assistant port Narula et al [17] have reported a series of 5 RAPDs performed with a mean operative time of 420 min and no peri-operative mortality.…”
Section: Robotic-assisted Pancreato-duodenectomymentioning
confidence: 99%
“…Reviews on robotic pancreatectomies report the average operative time for these operations to be 404+102 minutes, average blood loss 328+334 ml., conversion to open rate 10.6%, and a complication rate of 30.7% (31)(32)(33)(34).…”
Section: Robotic Hepatopancreaticobiliary System Surgerymentioning
confidence: 99%